December 2020 Newsletter - Coasters Association (2020)

Newsletter - Coasters Association (2020)

Newsletter - Coasters Association (2020)

Newsletter - Coasters Association (2020)

Newsletter - Coasters Association (2020)

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Executive Director's Report : April 2019 to March 2020 - Coasters Association (2020)
This report of activities of the Coasters Association Inc. have been prepared in order to provide the Board of Directors and membership with general information and summary of the work carried out since April 1st, 2019 to March 31st, 2020 (12 months), as outlined in the activities of the contribution agreement of Canadian Heritage.

Newsletter - Coasters Association (2020)

Newsletter - Coasters Association (2020)

A Portrait of the Territory Driving Innovation for a Stronger Future : A Depiction of the Coasters Association on the Lower North Shore, an Overview of the Region, a Breakdown of Each Community Profile and the Way Forward From Here - Coasters Association (2020)
What makes for a good quality of life varies from one community to another. This report presents some of the latest statistical measures that have been identified as important to the Lower North Shore. It explores issues like population decline, the economy and our social structures. This document was prepared for the Community Wellbeing Initiative (CWI). It provides a snapshot of the current state of wellbeing on the Lower North Shore based on selected indicators. Along with other measurements, these indicators form a baseline in which the success of the CWI can be assessed. They show where we are making progress, where we are falling behind, and what we can do - both as a region and as individuals - to improve quality of life.

AGM Minutes : Annual General Report - Coasters Association (2020)

Annual General Meeting : Coastal Summit Series 2020 - Coasters Association (2020)

Partnership Summit 2020 : Exploring Economic and Social Development - Coasters Association (Partnership Summit, 2020)

Recipe Book : Volume Two - Coasters Association (2020)

Sommet du partenariat 2020 : Explorer le développement économique et social - Coasters Association (Partnership Summit, 2020)

Un portrait du territoire - Coasters Association (2020)
Ce qui est considere comme une bonne qualite de vie varie d'une communaute a l'autre. Ce rapport presente certaines des plus recentes mesures qui ont ete identifiees comme importantes pour la Basse-Cote-Nord. II explore des enjeux comme le declin de la population, l'economie et les structures sociales. Ce document a ete prepare pour la Community Wellbeing Initiative (CWI). II fournit un portrait de l'etat actuel du mieux-etre en Basse-Cote-Nord, base sur des indicateurs choisis. Ces indicateurs torment, couples a d'autres mesures, une base a partir de laquelle le succes du CWI peut etre evalue. lls montrent les domaines dons lesquels nous faisons des progres, ceux ou nous sommes en retard et ils indiquent ce que nous pouvons faire, en tant que region et comme individus, pour ameliorer la qualite de vie.

Coastal Summit Report 2020 - Fequet, Shelley (2020)
A virtual Coastal summit was organized and carried out by the Coasters Association in the fall of 2020. A total of 156 individuals participated in a series of Zoom sessions which had two objectives. First, sharing information about the social and economic initiatives of the Coasters Association; and second, how to support the economic and social development of the Lower North Shore.
Keywords: Official Language Minority Community (OLMC)

Rapport sommet côtier 2020 - Fequet, Shelley (2020)
Un sommet du littoral virtuel a été organisé et réalisé par la Coasters Association à l’automne 2020. Au total, ce sont 156 personnes qui ont participé à une série de réunions Zoom qui visaient deux objectifs : tout d’abord, partager d l’information sur les initiatives sociales et économiques de la Coasters Association ; puis, déterminer la façon de soutenir le développement économique et social de la Basse-Côte-Nord.
Keywords: Official Language Minority Community (OLMC)